Findings from the observational COMPLY study in children and adolescents with ADHD: core symptoms, ADHD-related difficulties, and patients’ emotional expression during psychostimulant or nonstimulant ADHD treatment - Dittmann, Ralf; Banaschewski, Tobias; Schacht, Alexander; Wehmeier, Peter M. (ADHD Attention Deficit and Hyperactivity Disorders, 2014)
The aim of this study was to explore the course of attention-deficit/hyperactivity disorder (ADHD) core symptoms, ADHD-related difficulties, and emotional expression during ADHD pharmacotherapy and associations between them. This prospective, observational study examines pediatric patients with ADHD who newly initiated stimulant, atomoxetine or a combination of both treatments. Data were collected at baseline; weeks 1, 2, and 4; and months 3, 6, 9, and 12. Physicians rated ADHD core symptoms using the ADHD Rating Scale (ADHD-RS); patients, parents, and physicians rated ADHD-related difficulties using the Global Impression of Perceived Difficulties (GIPD) Scale; and patients and parents rated emotional expression using the Expression of Emotion Scale for Children (EESC). Results were analyzed using mixed model repeated measures. Associations are presented by Spearman’s correlations. Overall, 504 patients, mean age 9.6 years, 72.6 % males, were analyzed. Fifty percent of patients started atomoxetine, 49.0 % stimulant and 1 % a combination of both. ADHD-RS, GIPD, and EESC scores decreased significantly in both monotherapy groups. Correlations between ADHD-RS and parent- or physician-rated GIPD scores were at-best moderate and increased over time but remained low to moderate for patient-rated GIPD [patient, r = 0.43 (95 % CI 0.34, 0.51); parent, r = 0.58 (0.50, 0.64); physician, r = 0.55 (0.48, 0.62)]. Correlations between ADHD-RS and patient- or parent-rated EESC scores were low at baseline (r < 0.2) and increased over time mostly for parent ratings [patient, r = 0.35 (0.26, 0.44); parent, r = 0.41 (0.32, 0.50)]. These data support the effectiveness of ADHD pharmacotherapy. The at-best moderate correlations between ADHD core symptoms and ADHD-related difficulties or emotional expression assessed by different raters indicate potentially important patient outcomes beyond core symptoms.
Gesehen am 10.11.2020